The breaststroke pull-out technique: How to optimize performance
The study revealed evidence that the pull-out technique currently used by almost all elite breaststroke swimmers, both male and female, produced velocities well below the mean swimming speed for their breaststroke swimming, and provided an excellent benchmark for comparison. It also demonstrated that the traditional method of executing a breaststroke pull-out could be improved by 20 per cent in one session. This was accomplished by executing the pull-out phase sooner off the wall and by reducing the drag incurred during the pull-out and recovery phase. The velocity attained can match or exceed the swimmers mean velocity for breaststroke swimming, thus giving swim mers a way to optimize their performance for this technique. The subjects for this study were all highly skilled breast stroke swimmers (Sarah Miller and Matt Buck).